2000
DOI: 10.1021/ja9942540
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Characterization of Solution Oligomerization Process Mediated Gold−Gold Interactions. DFT Calculations on [Au2Ag2R4L2]nMoieties

Abstract: The optical properties of [Au 2 Ag 2 (C 6 F 5 ) 4 (OCMe 2 ) 2 ] n (1) have been studied in the solid state at room temperature and at 77 K and in acetone solution (5 × 10 -4 M). The crystal structure of 1, analyzed by X-ray diffraction, consists of polymeric chains formed by repetition of Au 2 Ag 2 moieties linked through short gold-gold interactions. The emission profile observed for 1 in dilute acetone solution (5 × 10 -4 M) is assignable to pentafluorophenyl localized ππ* excited states or from π-MMCT trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
119
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 143 publications
(132 citation statements)
references
References 55 publications
12
119
1
Order By: Relevance
“…Fernández et al [3] very thoroughly examined the origin of the photophysical properties of Au 2 (C 6 F 5 ) 4 Ag 2 (OCMe 2 ) 2 . At high concentrations and in the solid state the emission of this species originates from the aurophilic Au···Au intermolecular interactions; however, in dilute solution, the emission appears to arise from either ππ* or π-MMLCT excited state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fernández et al [3] very thoroughly examined the origin of the photophysical properties of Au 2 (C 6 F 5 ) 4 Ag 2 (OCMe 2 ) 2 . At high concentrations and in the solid state the emission of this species originates from the aurophilic Au···Au intermolecular interactions; however, in dilute solution, the emission appears to arise from either ππ* or π-MMLCT excited state.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established [1][2][3] that closed-shell, d 10 metal ions often exhibit attractive interactions. These interactions, although weaker than ionic bonds, are stronger than simple van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the reaction between NBu 4 [Au(C 6 F 5 ) 2 ] and AgClO 4 in acetone leads to a heterometallic extended linear chain of formula [Au 2 Ag 2 (C 6 F 5 ) 4 (Me 2 CO) 2 ] n . 38 Its crystal structure consists of an extended polymeric chain of tetranuclear Au 2 Ag 2 units formed through short gold-gold contacts of 3.1674(11) Å (Fig. 6).…”
Section: Supramolecular Gold-silver Complexes Built With Metallic mentioning
confidence: 99%
“…9). 38,41 Although, the anionic nature of this gold precursor could be the origin of its donor characteristics, our research group has found that the presence of only one perhaplophenyl group in the gold precursor produces similar potential in their reactions with silver salts. For instance, the neutral species [AuR(tht)] (R 5 C 6 F 5 , 3,5-C 6 Cl 2 F 3 , C 6 Cl 5 ) have been investigated in their reactions with silver trifluoroacetate.…”
Section: Supramolecular Gold-silver Complexes Built With Metallic mentioning
confidence: 99%